Foresight beyond the very next event: four-year-olds can link past and deferred future episodes - Redshaw, Jonathan; Suddendorf, Thomas (Frontiers in Psychology, 2013)
Previous experiments have demonstrated that by four years of age children can use information from a past episode to solve a problem for the very next future episode. However, it remained unclear whether four-year-olds can similarly use such information to solve a problem for a more removed future episode that is not of immediate concern. In the current study we introduced four-year-olds to problems in one room before taking them to another room and distracting them for 15 minutes. The children were then offered a choice of items to place into a bucket that was to be taken back to the first room when a five-minute sand-timer had completed a cycle. Across two conceptually distinct domains, the children placed the item that could solve the deferred future problem above chance level. This result demonstrates that by 48 months many children can recall a problem from the past and act in the present to solve that problem for a deferred future episode. We discuss implications for theories about the nature of episodic foresight.